A poética da heterogênese: acerca de dispositivos artísticos com aparatos computacionais - Leonardo da Silva Souza (2018)
Situated in the context of Technological Poetics, concerning the interlacings between Art, Science and Technology, this thesis discusses a possible poetics of heterogenesis, considering the artistic experimentations with computational devices. In order to start the discussion about the poetics of heterogenesis, we present two works created by Rafael Lozano-Hemmer (Mexico, 1967), Tape Recorders (2011) and Call on Water (2016), relating them to the trajectory of studies and experimentation in Art, Science and Technology of this author. From the study of Andreas Broeckmann (1997), we present the key terms for the discussion of heterogenesis as a characteristic of a poetics that involves Art and Technology: Algorithm (GOFFEY, 2008; KOWALSKI, 1979), Dispositive (FOUCAULT, 1979), Apparatus (BROECKMANN, 1997), Analog, Digital (ROBINSON, 2008) and the Heterogenesis (GOFFEY, 2009; DELEUZE, 2005). We consider the notion of heterogenesis suggested by Gilles Deleuze in several works, and discussed by Goffey (2009), as a form of thinking wich deals with connection of differences. In order to consider heterogeneity in the whole, we characterize the concept of dispositive as the set of heterogeneous components - in our case, the computational, aesthetic and political - connected through a strategy of heterogenization. We correlate strategy of heterogenization to artistic experimentation, in order to verify the computational apparatus' ability to exchange programmed behaviors with other non computational materials, generating heterogeneities. With special interest in this thesis, we characterize the apparatuses and computational devices as an integral part of a dispositive aimed at artistic experimentation, indicating the potential to produce sensations, percepts and affections, from the transference of behaviors between computational and non-computational material. In order to consolidate the proposed discussion, we describe ways of creating heterogeneous behaviors and how the artistic compositions occur with the exchange of technological behaviors with non-computational materials. Through an analysis of two experiments created, we detail the aesthetic composition with heterogenesis in Anatomy of a hacking (2016) and Improvr (2017). Thus, with heterogeneous behaviors, heterogeneous sensations are created, which in turn enable aesthetic compositions. Finally, such aesthetic compositions with sensations derived from heterogeneous behaviors of Art, Science and Technology support our notion of a poetics of heterogenesis.